Kinetic Analysis of Glucose with Wireless Magnetoelastic Biosensor - Gao, Xianjuan; Cai, Qingyun (Asian Journal of Chemistry, 2013)
A wireless remote-query disposable magnetoelastic biosensor was developed for the kinetic study of glucose. The sensor was fabricated by applying a magnetoelastic ribbon with a layer of pH-sensitive polymer and upon it a sensing film containing bovine serum albumin (BSA) and glucose oxidase (GOX). The GOX-catalyzed hydrolysis of glucose decreases the solution pH, resulting in the polymer shrinking and consequently the resonance frequency of the magnetoelastic sensor increasing. The kinetic parameters were measured to be 8.46 mM (Michaelis constant) and 769 Hz/min (maximum initial rate). A linear fitting was obtained between 2 and 15 mM of glucose with a regression coefficient of 0.99 (n = 5). The proposed sensor can determine 1.45 mM of glucose.